The effects of alloy composition and annealing time on microstructure and mechanical properties of Zr3Al-based alloys. (November 2015) - Li, J. H.; Gao, Y.; Liu, S.; Mao, L.; Zhang, F. C.; Li, Q.
Abstract : ZrAl alloys with three different Al contents (6.0, 7.0, 8.0 wt-%) were melted by non-consumable electric-arc furnace. X-ray diffraction and metallographic analysis were used to study the microstructure and phase composition of ZrAl alloys, then rockwell hardness and tensile properties were tested. The results showed that Al significantly enhanced the hardness of pure Zr, and hardness of as-cast ZrAl alloys increased with the increase of Al content. Homogeneous microstructure of Zr3 Al-based alloys could be obtained by annealing, and the annealing time must increase with the increase of Al content. With the increase of annealing time, grain size of Zr3 Al-based alloys increased, tensile strength and elongation decreased. This implied that when ensuring complete peritectoid reaction conditions, we should minimise annealing time to avoid coarse grain for the purpose of obtaining Zr3 Al-based alloys with excellent mechanical properties. In addition, annealing changed the fracture mode of ZrAl alloys from brittle to ductile.